Designing a mate choice program: Tactics trialed and lessons learned with the critically endangered honeycreeper, 'akikiki (Oreomystis bairdi). Issue 4 (28th March 2023) - Alverson, Donald P.; Martin, Meghan S.; Hebebrand, Christina T.; Greggor, Alison L.; Masuda, Bryce; Swaisgood, Ronald R.
Abstract: Practitioners have increasingly turned to conservation breeding to address species extinction. Breeding programs aim to maximize genetic diversity, but often genetic pairings are behaviorally incompatible, which can compromise offspring production. Allowing animals to choose their own mate can improve compatibility and increase the number and quality of offspring produced. However, designing mate choice protocols can be challenging when dealing with endangered species where little is known about their reproductive biology and behavior. We present the first experimental attempt to develop a mate‐choice program for the endangered Hawaiian honeycreeper, the 'akikiki ( Oreomystis bairdi ). We aimed to determine (1) which behaviors predict preference, (2) how best to observe preference, and (3) whether preference predicts successful socialization, nest building and egg production. We gave each female a choice between two males and assessed preference over multiple observations. Each female was then paired with a preferred or a nonpreferred male and their breeding outcomes were tracked. 'Akikiki paired with a preferred mate were more likely to lay eggs and had more eggs per clutch. We identify the optimal length, number, and complexity of observations for determining preference, thereby balancing the time investment of staff, while maximizing the potential reproductive output of the program. Abstract : Conservation breeding programs can be improved when animals are able to choose their own mates, but designing mate choice protocols is challenging with endangered species where little is known about their reproductive biology and behavior. We document and test a mate choice protocol for the critically endangered 'akikiki. We found preferred pairings laid more eggs, and examined ways to improve the efficiency of observation methods.